Directly writing flexible temperature sensor with graphene nanoribbons for disposable healthcare devices. Issue 37 (10th June 2020) - Gong, Xue; Zhang, Long; Huang, Yinan; Wang, Shuguang; Pan, Gebo; Li, Liqiang
Abstract : A flexible temperature sensor is developed by directly writing or mask spraying commonly-used paper with graphene nanoribbon ink. The sensor is ultralow cost, degradable, and highly promising as a disposable device for personal healthcare. Abstract : Disposable temperature sensors have great advantages in public health security and infectious disease control. However, complicated fabrication processes and poor performances persistently restrict their practical applications. In this paper, a flexible temperature sensor is firstly developed by directly writing or mask spraying commonly-used paper with a highly thermo-sensitive graphene nanoribbon (GNR) ink. The inexpensive, green materials and process endow the GNR sensors with the properties of being low cost, degradable and pollution free. The band gap and the local traps of GNRs, caused by the nanoscale effect and oxygen doping, make the sensor highly thermo-sensitive. The sensor also shows fast response, precise resolution and good bendable properties. As demonstrated, the sensor achieves monitoring of respiratory rate, measurement of body temperature, identification of human touch and constituting a 5 × 5 array for temperature mapping. These results demonstrate that the GNRs sensor is highly promising as an economical disposable device for personal healthcare and disease monitoring.